2020
DOI: 10.31557/apjcp.2020.21.4.1115
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Salivary S100A7 Levels in Stage I Oral Submucous Fibrosis: A Clinical and Laboratory Study

Abstract: Pakistan is one of the countries in SouthEast Asia that have a broad habit of areca nut and smokeless chewable tobacco because their products are readily accessible that leads to increased OSF incidence in this country

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…We found 92 DEGs in NFs and 698 DEGs in CAL27 cells. Some of the DEGs have previously been reported associated with OSF and/or OSCC, like S100A7 [ 33 36 ], RPS28 [ 37 ] and CYP26B1 [ 38 , 39 ]. Increased expression of CYP26B1 was identified in betel quid (BQ)-related OSCC tumor tissues, and could be a novel biomarker for BQ-related oral and pharyngeal cancers [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found 92 DEGs in NFs and 698 DEGs in CAL27 cells. Some of the DEGs have previously been reported associated with OSF and/or OSCC, like S100A7 [ 33 36 ], RPS28 [ 37 ] and CYP26B1 [ 38 , 39 ]. Increased expression of CYP26B1 was identified in betel quid (BQ)-related OSCC tumor tissues, and could be a novel biomarker for BQ-related oral and pharyngeal cancers [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that S100A7 was remarkably upregulated in ESCC and performed well as an independent prognostic factor. In addition, numerous studies have reported that S100A7 can not only function within the cell but can also be secreted and detected in serum (lung squamous cell carcinoma), 34 saliva (oral squamous cell carcinoma), 35 urine (melanoma), 36 and other body fluids. Moreover, S100A7 was upregulated in the serum of patients with lung squamous cell carcinoma 34 .…”
Section: Discussionmentioning
confidence: 99%
“…CD34 is a cluster of differentiation molecule that is seen on several cells inside the body. It is a glycoprotein that is present on the surface of the cell, which works as a cell-cell adhesion factor [ 8 , 9 , 10 ]. Cells that express CD34 are endothelial cells of blood vessels excluding lymphatics (except pleural lymphatics), mast cells, a sub-population of dendritic cells (which are factor XIIIa negative) in the interstitium and around the adnexa of the dermis of the skin.…”
Section: Introductionmentioning
confidence: 99%